2014
DOI: 10.5664/jcsm.3962
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Chinstrap in Treating Sleep Disordered Breathing and Snoring

Abstract: A chinstrap alone is not an effective treatment for OSA. It does not improve sleep disordered breathing, even in mild OSA, nor does it improve the AHI in REM sleep or supine sleep. It is also ineffective in improving snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, a randomized control trial found no efficacy in OSA or snoring in the general OSA population, possibly due to the elevation of the tongue base secondary to submental pressure from the device. 14,15 Lee et al describe the use of a MAS style oral appliance in a patient who did not achieve sufficient response to HGNS. They describe a good response with AHI of 3.5 down from 11.6 events/hour when the HGNS and MAS were used together as compared to the HGNS alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a randomized control trial found no efficacy in OSA or snoring in the general OSA population, possibly due to the elevation of the tongue base secondary to submental pressure from the device. 14,15 Lee et al describe the use of a MAS style oral appliance in a patient who did not achieve sufficient response to HGNS. They describe a good response with AHI of 3.5 down from 11.6 events/hour when the HGNS and MAS were used together as compared to the HGNS alone.…”
Section: Discussionmentioning
confidence: 99%
“…The chinstrap is a more controversial device, which has been shown to be successful in individual case reports for people with retrolingual/supraglottic collapse. However, a randomized control trial found no efficacy in OSA or snoring in the general OSA population, possibly due to the elevation of the tongue base secondary to submental pressure from the device . Lee et al describe the use of a MAS style oral appliance in a patient who did not achieve sufficient response to HGNS.…”
Section: Discussionmentioning
confidence: 99%
“…While one study one showed no objective improvement in AHI [3], when looking at the chin strap utilized by the researchers, it is obvious that this device is neither stable nor lifting of the chin, but quite flimsy with the incorrect vector of lift. If the device fails to close the jaw comfortably during the night, the device is automatically a failure.…”
Section: Temporary Mouth-closure Devicesmentioning
confidence: 98%
“…Jaw-closure wearable devices (Garments/straps/tape) 2. Intra-oral appliances to support the jaws Long-term Mouth-closure solutions 3. Muscle re-training exercises (Myofunctional therapy) 4.…”
mentioning
confidence: 99%
“…It has been shown that chinstrap reduces mouth leak by closing the mouth during CPAP application, and therefore decreases the arousal index . However, the same study has shown that chinstraps may also exacerbate snoring and, in rare cases, can worsen the respiratory disturbance index . It is also uncomfortable for many patients and can cause unwanted dental side effects like tooth chipping (Fig.…”
Section: Interface‐related Side Effectsmentioning
confidence: 99%